A novel three-dimensional mechanical metamaterial with compression-torsion properties. (15th October 2019) - Zhong, Rongchang; Fu, Minghui; Chen, Xuan; Zheng, Binbin; Hu, Lingling
Abstract: A new design of a 3D compression-torsion mechanical metamaterial is proposed based on the chiral mechanism of inclined rods converting axial compression (or tension) into torsion. Experiments and numerical simulations are employed to investigate the compression-torsion properties of the new proposed metamaterial under uniaxial compression. Results show that it possesses excellent compression-torsion properties compared to previously reported 3D compression-torsion metamaterials. Moreover, the torsion angle of the proposed metamaterial under compression can maintain a large value even when the transverse cell number N = 9 . By contrast, the torsion angle of structures reported in references declined rapidly with the cell number, and the compression-torsion properties nearly vanished when N = 5 . These outstanding properties of the proposed metamaterial are due to the better compression-torsion properties of the unit cell and weaker transverse constraint among cells. The latter reason also contributes to an interesting phenomenon wherein the torsion angle first increases and then declines with the transverse cell number N, which is much different from the monotonically decreasing trend of other 3D compression-torsion metamaterials. The main factors affecting the compression-torsion properties of 3D metamaterials are revealed and discussed in detail, shedding light on the design of 3D metamaterial with outstanding compression-torsion properties.